Desigualdades no mercado de trabalho e pandemia da Covid-19 - Joana Sim\~oes Costa; Ana Luiza Neves de Holanda Barbosa; Marcos Hecksher (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The aim of this study is to investigate three relevant dimensions of Brazilian inequality in the labor market, gender, race and age, in the period 2012-2020. More specifically, we analyze how these statistics were affected by the crisis due to Covid-19. It is observed that inequalities in participation, unemployment, occupation and informality rates are not reduced during the 2020 crisis. On the contrary, there is an increase in the difference of employment to population ratio by race and age. The results also indicate that 2020 is characterized by an unusual increase in the chances of job loss and a reduction in the chances of getting a job. It is important to note that even when controlling for other personal or job characteristics, women, blacks and young people are more likely to lose their jobs. Nonetheless, this disadvantage is not specific of the 2020 crisis.
Keywords: J15; J16; J21; 330; Covid-19; inequality; labor market; gender; race; age